ANTI-INFLAMMATORY ROLE OF ANNONA MURICATA FRUIT EXTRACT ON CYTOARCHITECTURE OF TESTOSTERONE INDUCED PROSTATIC HYPERPLASIA IN MALE WISTAR RAT - Adegoke, Adebiyi Aderinola; Dare, Babatunde Joseph; Adekomi, Damilare Adedayo; Fadare, Mayowa Uthman; Taiwo, Folashade Adekemi; Amusa, Oluwadamilola Oluwatobiloba; Adegboyega, H. T.; Adio, M. P.; Ebiwonjumi, Adetunji Segun; Ojo, Waliu Adetunji (FUDMA Journal of Sciences, 2025)
An increase in the prostate’s size that is not malignant is identified as benign prostatic hyperplasia (BPH), characterized by proliferation of the cellular membranes of the prostate, which leads to constriction of urine flow, abdominal pain, dysuria, urinary hesitancy, urinary intermittency, and nocturia. Hence, this study is designed to investigate the curative effect of Annona Muricata Extract (AME) on the prostate of testosterone-induced prostate hyperplasia and prostate as an organ. 20 male Wistar rats were randomly grouped into four groups of 5 animals per group. Group A used as control were given 0.5 ml normal saline (NS), Group B were administered 15mg/kg testosterone + extract (TEST + AME), Group C were administered 15mg/kg testosterone + extract (Recovery), Group D were administered 15mg/kg testosterone only (TEST). Statistical analysis was done using GraphPad Prism. The result revealed a considerable change in body weight of group treated with testosterone and Annona muricata (p value<0.001), prostatic (p value<0.0001) weight and testicular weight (p value<0.0014). Morphologically, prostatic collagen deposition and thick prostatic epithelium caused by testosterone administration were significantly reversed. There is regeneration of seminiferous tubules and interstitial spaces in testicular architecture after the administration of Annona muricata. In conclusion, this study has shown that Annona muricata with its rich antioxidants, makes it a strong alternative therapy in reversing the inflammation of any source in the system, as it is evident in the outcome of statistical analysis and histology.